"W.I. Lenin im Kreise von Delegierten des III. Kongresses des Kommunistischen Jugendverbandes (1920)" - Belousov, P.,
"W.I. Lenin im Kreise von Delegierten des III. Kongresses des Kommunistischen Jugendverbandes (1920)".